Stéréotypes et identité narrative des personnages dans Au commencement était la mer, de Maïssa Bey - Ait Challal, Salah (Romanica Silesiana, 2021)
In this contribution, we try to show how Maissa Bey tells, through stereotypical linguistic and narrative categories, the experience of emblematic characters carrying narrative identities contradictory, in an Algerian society in crisis. These identities reveal conflicts dealing with the underestimation of the female gender.